Comparison of Contrast-Enhanced MRI Using Hepatocyte-Specific Contrast with Contrast-Enhanced CT in Evaluation of Hepatobiliary Space-Occupying Lesions - Pratap , Vijay; Malhotra , Ankur; Chandak, Shruti (Biomedical Sciences and Clinical Medicine, 2026)
Objective This study aimed to evaluate the diagnostic accuracy of multiphasic contrast-enhanced computed tomography (CECT) and contrast- enhanced magnetic resonance imaging (CEMRI) in assessing hepatic mass lesions. Methods A cohort of 120 patients underwent imaging with both CEMRI and CECT to compare their diagnostic capabilities. Findings were analyzed for lesion size, enhancement patterns, sensitivity, specificity, and predictive values. Statistical tests were conducted to assess the significance of differences between the modalities, with p-values reported for critical metrics. To ensure consistency and minimize bias, a standardized imaging protocol was followed, and radiology experts independently reviewed all images. Results CEMRI demonstrated higher sensitivity (90%) and specificity (87%) compared to CECT (85% and 80%, respectively), with statistically significant differences (p < 0.05). CEMRI also outperformed CECT in posi- tive predictive value (88% vs. 82%) and negative predictive value (90% vs. 84%). While the mean lesion size detected by CEMRI (4.0 ± 2.0 cm) was slightly smaller than that detected by CECT (4.4 ± 2.2 cm), the difference was not statistically significant (p = 0.45). Additionally, CEMRI identified 112 lesions compared to 108 lesions detected by CECT, further highlighting its superior diagnostic accuracy, particularly in detecting heterogeneous lesions. Conclusion CEMRI outperforms CECT in diagnostic sensitivity, specificity, and predictive values, making it the preferred modality for lesion detection and characterization. However, both modalities performed similarly in assessing lesion size and total lesion count. These findings underscore the value of CEMRI in clinical scenarios requiring detailed lesion evaluation. Future studies with larger cohorts and a broader range of pathologies are recommended to confirm and extend these results for greater clinical applicability.